The visuospatial abilities of HIV positive adolescents on antiretroviral treatment in South Africa. - Greenslade, Daniel John (My University, 2014)
This researched aimed to explore the effects of the Human Immunodeficiency Virus (HIV) upon the visuospatial abilities of HIV-positive adolescents on antiretroviral treatment in South Africa. The literature suggests that the neurology responsible for visuospatial abilities (specifically various white-matter tracts in the brain) is very susceptible to the damaging effect that HIV has on the brain. The research sample consisted of vertically transmitted HIV-positive adolescents, on first line antiretroviral treatment, with a HIV-negative control group comparable on age and SES. The results indicated that there is a significant difference in the visuospatial abilities between adolescents with and without HIV. The expressions of these deficits were displayed differently between males and females, highlighting a differing developmental neurology, and the effect of HIV upon it. The viral strength and health of the immune system were also examined as variables and illuminated interesting results. Overall, the research illustrates the negative effect that HIV has upon developing neurology and the subsequent effects on visuospatial abilities.
Keywords: Human Immunodeficiency Virus (HIV); Antiretrovirals (ARV); Visuospatial abilities